(3GdCfhGQ GdSGaQI aj fUQI GdCTGYQIs - (3CHh GdaOG ESeGYjd GdfjSGHhQjs
(3ChdgG (B:s
(3hHYO abO SCdfi HYV GdGFeI Cf CUfa dg eG JbQQ Ydjg GdGUWdGM ai efGXQI Gdabg HfjSGHhQ HjffG eYGTQ CUMGH ehdGfG GdGeGe eMi GdOjf MLI GdGSdGe CHj SYO eMeO Hf jMji JYeOg Gdgd HQVhGfg s
(3BNQgG (B:s
(3hEfeG jNGda ai GdbhI hGdhge hbOeJ ai GdbhI hGddg GYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3GdHOjQi (B_ (3HGdbOS s
Keywords: (3GdJhMjO hGdedd hGdfMds